Mucoadhesive Nanoparticles Enhance the Therapeutic Effect of Dexamethasone on Experimental Ulcerative Colitis by the Local Administration as an Enema - Dong K; Deng SJ; He BY; Guo ZY; Guan ZL; Leng X; Ma RR; Wang DY; Xing JF; You CY (Dove Medical Press, 2023)
Kai Dong,1,2 Shu-Jing Deng,2 Bin-Yang He,2 Zi-Yang Guo,2 Ze-Lin Guan,2 Xue Leng,2 Rui-Rui Ma,2 Dan-Yang Wang,2 Jian-Feng Xing,2 Cui-Yu You1 1Department of Pharmacy, The First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, Shaanxi, People's Republic of China; 2School of Pharmacy, Xi'an Jiaotong University, Xi'an, Shaanxi, People's Republic of ChinaCorrespondence: Jian-Feng Xing, School of Pharmacy, Xi'an Jiaotong University, 76 Yanta West Road, Xi'an, 710061, Shaanxi, People's Republic of China, Tel +86-29-82655139, Fax +86-29-82655139, Email xajdxjf@mail.xjtu.edu.cn Cui-Yu You, Department of Pharmacy, The First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, Shaanxi, People's Republic of China, Tel +86-29-85323241, Fax +86-29-85323240, Email ycy720123@163.comBackground: As the first-line drug to treat ulcerative colitis (UC), long-term use of glucocorticoids (GCs) produces severe toxic and side effects. Local administration as enema can increase the local GCs concentrations and reduce systemic exposure to high oral doses by directly delivering GCs to the inflammation site in the distal colorectum. However, UC patients are often accompanied by diarrhea, leading to the short colonic residence time of GCs and failure to exert their function fully.Purpose: A kind of mucoadhesive nanoparticles (NPs) loading different dexamethasone derivatives (DDs) were developed, which could attach to the positively charged inflammatory colonic mucosa through electrostatic adsorption after administered by enema, thereby improving the local concentration and achieving effective targeted therapy for UC.Methods: Two DDs, dexamethasone hemisuccinate and dexamethasone phosphate, were synthesized. In NPs preparation, The core PEI-DDs NPs were built by the electrostatic adsorption of DDs and the cationic polymer polyethyleneimine (PEI). Then, the natural polyanionic polysaccharide sodium alginate (SA) was electronically coated around NPs to construct the final SA-PEI-DDs NPs, followed by the in vitro stability and release tests, in vitro and in vivo colonic mucosal adhesion tests. In the in vivo anti-UC test, the experimental colitis mice were induced by 2,4,6-trinitrobenzenesulfonic acid. The body weight and disease activity index changes were measured, and the myeloperoxidase activity, pro-inflammatory cytokines concentration, and hematoxylin and eosin staining were also investigated to evaluate the therapeutic effect of NPs.Results: The structures of two DDs were demonstrated by 1H-NMR and MS. Both NPs were negatively charged and achieved high loading efficiency of DDs, while their particle sizes were significantly different. NPs showed good stability and sustained release properties in the simulated colonic environment. Moreover, the negative charge on the of NPs surface made them easier to adhere to the positively charged inflammatory colonic mucosa, thereby enhancing the enrichment and retention of DDS in the colitis site. Furthermore, the NPs exhibited better therapeutic effects than free Dex on the experimental colitis mice induced by TNBS through the enema rectal.Conclusion: These results indicated the mucoadhesive NPs as a kind of novel nano-enema showed great potential to achieve efficient treatment on UC.Keywords: ulcerative colitis, glucocorticoids, mucoadhesive, polyethyleneimine, sodium alginate